Endocrinopathies' Prevalence in Beta-Thalassemia Major Patients - Al-Zamili, Sadeq Lafta Mousa (Universitas Muhammadiyah Sidoarjo, 2025)
Chronic anemia is a hallmark of thalassaemia major, a hereditary hemoglobinopathy. Iron deposits in a variety of tissues, including endocrine glands, as a result of excessive iron overload and inadequate chelation. Calculate the number of patients with thalassemia major who have endocrinopathies. The research design used in this study is an observational retrospective cohort. All BTM patients older than two who visited the Dubai Thalassemia Center between December 2023 and June 2024 had their electronic medical records searched for retrospective data. This evaluation comprised fasting glucose, morning cortisol, bone profile (including parathyroid hormone), pituitary and gonadal function, and thyroid function. In order to rule out diabetes mellitus, hypogonadism, hypothyroidism, hypoparathyroidism, and hypoadrenalism, these profiles were examined. Forty individuals with transfusion-dependent thalassemia had an average age of 17.43 ± 2.76 years. Of them, 53.3% were women. Approximately 76.92% had an endocrine problem of some kind. The most frequent endocrine presentation, occurring in 50% of individuals under the age of 20, was hypogonadotropic. Hypoparathyroidism (10.0%), hypothyroidism (3.3%), and glucose intolerance (26.7%) were present in one-third. Among adult Iraqi patients with beta-thalassemia, endocrine problems are highly prevalent. This highlights the significance of monitoring for early detection and replacement therapy, as well as awareness for their development. There was no correlation seen between serum ferritin and the onset of endocrinopathy. Highlights: Endocrinopathies were highly prevalent (76.9%) among beta-thalassemia major patients, with hypogonadism being the most common (50%). Additional endocrine disorders included glucose intolerance (26.7%), hypoparathyroidism (10%), and hypothyroidism (3.3%). Findings underscore the need for routine endocrine monitoring and early intervention to improve quality of life in thalassemia patients.